21st century competencies of teachers in teacher education institutions: Basis for designing faculty development program - Julie Ann B. Real (Northern Negros State College of Science and Technology (NONESCOST), 2022)
The role of teachers in the teaching-learning process is crucial. Students flourish when instruction and learning are at their finest. Competent teachers are needed to achieve successful teaching and fruitful learning. The main objective of this study is to assess the teachers' competencies in selected public and private Teacher Education Institutions (TEIs). It covered 1,770 respondents: 95 from teachers, 1,658 from students and 17 from superiors. Teacher-respondents were asked to evaluate the level of their teaching competencies. To make the study more consistent, their students, and superiors were also asked to evaluate them. The Teacher-respondents were evaluated using the five-point Likert scale. The statistical tools used in this research were Frequency, Percentage, Weighted Mean and ANOVA. Findings revealed that when the three groups of respondents were asked to evaluate the level of teachers' competency, they evaluated the teachers as 'Very competent' in terms of the competency indicators. Furthermore, based on the findings, there is no significant difference in the level of teachers' teaching competencies as perceived by the three sets of respondents. It is concluded that the three groups of respondents evaluated that teachers manifest high degree of success in performing instructional and other duties in teaching. This is based on the computed figures in the findings, which show that they rated the teachers as very competent in delivering the teaching competency indicators. Although, the respondents evaluated the teachers as very competent in teaching, there are competency-indicators that should be given attention, particularly the indicators which were lowly ranked.